Knowledge management in construction companies : development of a web-based database system - Karataş, Cenap Göktuğ. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
Companies struggle against complex and dynamic conditions in order to survive in their business settings. Being in the knowledge era, learning has been accepted as one of the main sources of sustainable competitive advantage. Organizational learning (OL) is a set of activities to obtain organizational memory (OM) by acquiring, sharing, interpreting, integrating and institutionalizing knowledge. OM is exploited by the companies in strategic decision-making process, which makes OL a critical concept. The major objective of this study is to explore how construction companies create OM and how they exploit this asset in project management activities. In this context, a questionnaire survey is conducted with Turkish construction companies. Findings of the survey are discussed in detail. The survey revealed the strengths and weaknesses of construction companies in terms of their OL competence. One of the key findings is that companies are successful at acquiring knowledge but they have difficulties at storing and sharing the acquired knowledge within their organizations. Although construction companies are aware of web-based database systems, they do not effectively use them. In order to meet the requirements of the industry in terms of effective learning and creation of OM, a web-based database system is developed to assist construction companies in making informed decisions in project and corporate management. This tool is also proposed to increase the OL competence of construction companies through the provision of all knowledge management activities.
Keywords: Knowledge management -- Case studies.; Information management systems -- Case studies.